Optimizing Surau as an Education Center in the Pandemic Period: (Community-Based Research) - Rozaanah Rozaanah; Muhammad Iqbal; Fakhrurrozi Fakhrurrozi; Ade Muhammad Ritonga; Ahmad Afandi (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
Community service activities are a community service activity that is needed by students to hone student skills and personalities so that they can go directly to the community. Therefore the KKL conducted by STAI AS-SUNNAH students aims so that all elements of society can participate in this activity by "Turning Ramadan in the Middle of Covid-19". This activity was carried out in West Sumatra to be precise in Solok, Tanah Datar Regency, Bukittinggi, Payakumbuh, and Fifty Cities Regency. The community participation in this activity, thank God, is quite a lot. Because many problems are spread in the community in the form of Tauhid, tahsin and tahfidz, scientific cycles, and other religious activities, we have taken several programs related to things that are being needed by the community in the hope that after holding the KKL it will benefit the community and increase knowledge. public knowledge, especially in the field of religion. The methods used in these activities are online and offline. And the result of this activity is that people know tauhid correctly, know the correct makharijul letters and tajwid, can add memorization and memorize memorization, and know knowledge about Islam such as the nature of ablution and the prayers of the prophet sallahu 'alaihi wa sallam, know surah in prayer and other religious sciences.